2009
DOI: 10.3748/wjg.15.1381
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of p53 over-expression and alteration in p53 gene detected by polymerase chain reaction-single strand conformation polymorphism in adenocarcinoma of gastric cancer patients from India

Abstract: AIM:To study the alterations in p53 gene among Indian gastric cancer patients and to correlate them with the various clinicopathological parameters. METHODS:A total of 103 gastric cancer patients were included in this study. The p53 alterations were studied by both immunohistochemical method as well as polymerase chain reaction (PCR)-single strand conformation polymorphism (SSCP) analysis. We only studied four (exon 5, 6, 7, and 8) of the 11 p53 exons. The alterations in p53 were also correlated with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We had shown significant association of p53 expression and alterations with histological grades patients (Karim et al, 2009;Sadeghi et al, 2013). Alteration of p53 gene has been reported controversial with any age group.…”
Section: Discussionmentioning
confidence: 99%
“…We had shown significant association of p53 expression and alterations with histological grades patients (Karim et al, 2009;Sadeghi et al, 2013). Alteration of p53 gene has been reported controversial with any age group.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that tobacco, alcohol, different food habit, infection etc. promote the occurrence of most of the cancers including stomach cancer mutations play an important role (Renault et al, 1993;Tamura et al, 1999;Karim et al, 2009). Several studies have suggested that a mutant allele promotes transformation by inactivating normal p53 function in a dominant-negative fashion (Finlay et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The estimated newly diagnosed cases were 23,785 in men and 11,819 in women. 1 The etiology of gastric cancer is a complex multistep process characterised by histopathologic precursor lesions and molecular genetic alterations. The p53 is a tumor suppressor gene, located on short arm of chromosome 17p 13.1 and plays a pivotal role in regulating cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…The p53 is a tumor suppressor gene, located on short arm of chromosome 17p 13.1 and plays a pivotal role in regulating cell growth. [1] p53 mutation is commonly encountered in many human cancers. Frequency of p53 overexpression in gastric adenocarcinoma is 26 to 65%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation